HUBUNGAN PENGETAHUAN DAN SIKAP IBU PADA ANAK USIA 3-5 TAHUN DENGAN PELAKSANAAN TOILET TRAINING DI WILAYAH KERJA PUSKESMAS RATU AGUNG KOTA BENGKULU - Yeni Eliyanti (Jurnal Sains Kesehatan, 2017)
One of the tasks of development is to form self-reliance, discipline, and emotional sensitivity in children. To achieve the task of development of one of them can be done via Toilet training early. Toilet training is the first step into a standalone personal child. The problem in this research are still mothers who have not been able to apply in his toilet training. The purpose of the study is the relationship of knowledge and attitude of the mother in children aged 3-5 years with the implementation of toilet training. This type of research is cross sectional.                        A population of 641 people and sampling by purposive sampling as many as 87 people. Data used in the study is the use of primary data. Analysis of the data in this study using univariate and bivariate data analysis with chi square statistic methods at significance level of 0.05. The results of this study are almost half of respondents (41.4%) who have less knowledge, almost half of respondents (47.1%) have unfavorable attitudes, almost half of respondents (40.2%) implementation toilet training less There is a relationship of knowledge and attitude of mothers in children aged 3-5 years with the implementation of toilet training. This study is expected for health care workers in posyandu who knows about the importance of implementing the toilet training should provide information to mothers who have children aged 3-5 years. Keywords : behaviour of mothers, knowledge,  toilet training